„Ekologizm” jako nowy nurt polityczny. Implikacje filozoficzno-etyczne - Mariusz Ciszek (Studia Ecologiae et Bioethicae)
The author tries to make an attempt to define the term „ecologism” because of its equivocality. For some authors, it is an idea, which has to be included in life to protect people and the world before extermination, whereas for others it is a contemporary variety of an ideology which could be quite dangerous for a man. The author defines it as treating ecologism as a new political stream near to conservatism, liberalism, and socialism. Taking into consideration the philosophical and ethical categories using in the environmental philosophy the author explains that ecologism should be connected with the anthropocentric model for environmental ethics, then it will not be dangerous for a man. This ethical stream can also be...with the paradigm of balanced development.